2017
DOI: 10.4103/2249-4863.220025
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity pattern and its sociodemographic determinants among elderly population of Raichur district, Karnataka, India

Abstract: Context:India is an “aging nation” with 7.7% of its population being above 60 years of age. It has resulted in a rise of both physical and mental health morbidities.Aims:This study aimed to gather information regarding the morbidity pattern and its sociodemographic determinants among the elderly residing in the rural villages of Raichur, to understand the need for geriatric health-care facilities.Settings and Design:This community-based cross-sectional study was carried out in six rural villages of Raichur Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 4 publications
5
19
1
Order By: Relevance
“…This is found to be similar to George LS et al findings. 21 In current study, majority of the study population doesn't know about family history of some chronic diseases, whereas those having family history, diabetes was the commonest (5.83%), followed by asthma (5.74%), which was similar to Srinivas PJ 16 who found most common history of previous illness was hypertension 12% and diabetes mellitus 6% in both rural and urban areas. Present study showed that tobacco chewing (45.23%) as the commonest form of addiction, while (34.66%) are addicted to smoking.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…This is found to be similar to George LS et al findings. 21 In current study, majority of the study population doesn't know about family history of some chronic diseases, whereas those having family history, diabetes was the commonest (5.83%), followed by asthma (5.74%), which was similar to Srinivas PJ 16 who found most common history of previous illness was hypertension 12% and diabetes mellitus 6% in both rural and urban areas. Present study showed that tobacco chewing (45.23%) as the commonest form of addiction, while (34.66%) are addicted to smoking.…”
Section: Resultssupporting
confidence: 59%
“…Present study showed that tobacco chewing (45.23%) as the commonest form of addiction, while (34.66%) are addicted to smoking. George et al, 21 study showed that smoking tobacco in (31.2% ) as the commonest form of addiction, while (13.8%) use nonsmoke tobacco (chewable form such as khaini, gutkha etc.) and (12.7%) addicted to alcohol in their study.…”
Section: Resultsmentioning
confidence: 99%
“…[24] In our study, it was seen that those older than 55 years had an increase in distress score post lockdown, though not statistically significant. Most of them are likely to be suffering from one or more medical morbidity [25] and it is known that the prognosis for such individuals if infected, is poorer. Fear of quarantine, hospitalization, intensive unit care, ventilator care, etc., would be responsible for their distress.…”
Section: Psychological Distress and Lockdownmentioning
confidence: 99%
“…Morbidities such as acid peptic diseases, constipation, Visual impairment, senile deafness, kidney disorder and arthritis were associated with functional limitations was found to be statistically significant but there was difference in a study conducted in North India by Joshi et al showed that elderly participants with higher morbidity had increasing disability. 13,14…”
Section: Regression Analysis To Predict the Risk Factor Of Functional Limitationsmentioning
confidence: 99%